EL QUE SE CASA ¿QUIERE CASA? EXPERIENCIA DE RELOCALIZACIÓN EN UN PROYECTO DE VIVIENDA DE INTERÉS SOCIAL - Arrieta Salas, Carlos (Universidad de Costa Rica, 2018)
This article analyzes the story of a conflictive process of relocation of almost one hundred families in a project of social interest housing located in Vera Cruz, a neighborhood near the southern border of the country. The participatory action research methodology was applied for almost two years and resulted in the identification of three main factors related to the psychosocial problems appearing in the process: the elimination of theparticipation of the beneficiaries, the prevalence of a conception of finished housing and the dis-articulation between the differences of those responsible for the development of this project.